Explore combined use of transcranial direct current stimulation and cognitive training on executive function after stroke - Yuan-Wen Liu; Zhong-Hua Chen; Jing Luo; Ming-Yu Yin; Li-Li LI; Yu-De Yang; Hai-Qing Zheng; Zhen-Hong Liang; Xi-Quan Hu (Medical Journals Sweden, 2021)
Objective: To explore the effects of transcranial direct current stimulation combined with cognitive training on executive function and activities of daily living performance among stroke patients. Methods: A total of 50 subjects were enrolled and randomly allocated into 2 groups of 25 each. The real-transcranial direct current stimulation group was simultaneously subjected to transcranial direct current stimulation and cognitive training, while the sham-transcranial direct current stimulation group was simultaneously subjected to sham transcranial direct current stimulation and cognitive training. At baseline, and after treatment, each subject was assessed with the Wisconsin Card Sorting Test (WCST), Stroop Color-Word Test (SCWT), Digital Symbol Test (DST), Mini-mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA) and Activities of Daily Living Scale (ADLs). Results: After treatment, the gains in most indices of WCST, SCWT, DST, MMSE, MoCA and ADLs in the real-transcranial direct current stimulation group were significantly higher than those in the sham-transcranial direct current stimulation group (p<0.05). Nonetheless, no significant differences were noted in the gains in SCWT (including only Part A time and error, and Part B time) and activities of daily living (including only basic activities of daily living) between the 2 groups (p>0.05). Conclusion: Transcranial direct current stimulation combined with cognitive training was found to significantly enhance executive function and instrumental activities of daily living performance among stroke patients.